2002
DOI: 10.1210/jcem.87.2.8214
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Is Associated with Increased Circulating Level of Thrombin-Activatable Fibrinolysis Inhibitor in Type 2 Diabetic Patients

Abstract: Hypofibrinolysis is a common finding in patients with diabetes mellitus (DM) and obesity and a risk factor for the development of cardiovascular disease. Recently, a new potent inhibitor of fibrinolysis, the thrombin-activatable fibrinolysis inhibitor (TAFI) has been isolated and characterized from human plasma. The present study was undertaken to assess the activity and circulating level of TAFI and its relation to fibrinolytic function and obesity in patients with type 2 DM. Fifty-seven patients with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 26 publications
5
71
0
3
Order By: Relevance
“…Elevated plasma levels of TAFI are associated with increased risk of cardiovascular diseases [116120]. In diabetes, TAFI levels appear to correlate with HbA1c, indicating an association between TAFI levels and poor glycaemic control [121]. Plasma concentration and activity of TAFI are significantly increased in T2DM patients compared with healthy controls, particularly in obese patients [121].…”
Section: Mechanisms Of Hypofibrinolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated plasma levels of TAFI are associated with increased risk of cardiovascular diseases [116120]. In diabetes, TAFI levels appear to correlate with HbA1c, indicating an association between TAFI levels and poor glycaemic control [121]. Plasma concentration and activity of TAFI are significantly increased in T2DM patients compared with healthy controls, particularly in obese patients [121].…”
Section: Mechanisms Of Hypofibrinolysismentioning
confidence: 99%
“…In diabetes, TAFI levels appear to correlate with HbA1c, indicating an association between TAFI levels and poor glycaemic control [121]. Plasma concentration and activity of TAFI are significantly increased in T2DM patients compared with healthy controls, particularly in obese patients [121]. TAFI levels have also been linked in T2DM to the presence of microvascular complications manifesting as microalbuminuria [122, 123].…”
Section: Mechanisms Of Hypofibrinolysismentioning
confidence: 99%
“…The latter were investigated in diabetes type 1 and 2, but less is known about them in GDM. Hori et al [20] demonstrated that the plasma concentration and activity of TAFI were significantly higher in patients with type 2 diabetes than in healthy controls [20]. Moreover, they showed that the plasma TAFI levels were independently and significantly correlated with glucose intolerance (HbA 1c ), and with obesity (BMI, visceral fat area) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Hori et al [20] demonstrated that the plasma concentration and activity of TAFI were significantly higher in patients with type 2 diabetes than in healthy controls [20]. Moreover, they showed that the plasma TAFI levels were independently and significantly correlated with glucose intolerance (HbA 1c ), and with obesity (BMI, visceral fat area) [20]. Among patients with type-1 diabetes although Antovich et al [21] reported a decrease in TAFI antigen levels, Harmanci et al [22] did not find any alterations in TAFI antigen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both the level and the activity of plasma TAFI in patients with T2DM are reported to be significantly higher than those in healthy individuals [2]. Both the level and the activity of plasma TAFI in patients with T2DM are reported to be significantly higher than those in healthy individuals [2].…”
Section: Introductionmentioning
confidence: 95%